2017
DOI: 10.1093/protein/gzw073
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the peroxygenative:peroxidative activity ratio in the unspecific peroxygenase fromAgrocybe aegeritaby structure-guided evolution

Abstract: Unspecific peroxygenase (UPO) is a heme-thiolate peroxidase capable of performing with high-selectivity C-H oxyfunctionalizations of great interest in organic synthesis through its peroxygenative activity. However, the convergence of such activity with an unwanted peroxidative activity encumbers practical applications. In this study, we have modified the peroxygenative:peroxidative activity ratio (P:p ratio) of UPO from Agrocybe aegerita by structure-guided evolution. Several flexible loops (Glu1-Pro35, Gly103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Some of the neutrally evolved variants in our study showed slight changes in the peroxygenative/peroxidative ratio that were dependent on the substrate tested. In this regard, recent findings ( 11 , 13 , 39 ; unpublished data) indicate that the peroxygenative/peroxidative ratio is mostly dependent on the nature of the targeted substrates, which defines the access to the heme channel and the residence time at the binding site for proper oxygenation/oxidation, rather than the existence of catalytic radical-forming residues at the protein surface to work through a long-range electron-transfer pathway to the heme, as described for ligninolytic peroxidases ( 35 ). The variants with the greatest thermostabilities (variants 16.5 and 6.1) displayed overall decreases in catalytic efficiencies ( k cat / K m ), which may be connected to a putative tradeoff between activity and stability that can be circumvented by different engineering strategies (reference 36 and references cited therein).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Some of the neutrally evolved variants in our study showed slight changes in the peroxygenative/peroxidative ratio that were dependent on the substrate tested. In this regard, recent findings ( 11 , 13 , 39 ; unpublished data) indicate that the peroxygenative/peroxidative ratio is mostly dependent on the nature of the targeted substrates, which defines the access to the heme channel and the residence time at the binding site for proper oxygenation/oxidation, rather than the existence of catalytic radical-forming residues at the protein surface to work through a long-range electron-transfer pathway to the heme, as described for ligninolytic peroxidases ( 35 ). The variants with the greatest thermostabilities (variants 16.5 and 6.1) displayed overall decreases in catalytic efficiencies ( k cat / K m ), which may be connected to a putative tradeoff between activity and stability that can be circumvented by different engineering strategies (reference 36 and references cited therein).…”
Section: Resultsmentioning
confidence: 91%
“…Such approaches conceptually unify the fields of chemical catalysis, photocatalysis, and biocatalysis, with the aim of updating longstanding industrial processes through the inclusion of ad hoc engineered, efficient, and stable UPO variants ( 6 8 ). In this regard, advances in UPO design have recently been achieved through directed evolution, addressing aspects from its heterologous functional expression in yeast to the synthesis of chemicals and pharmaceutical compounds ( 9 13 , 39 ). These evolutionary enterprises have been carried out by adaptive evolution, i.e., the construction and exploration of mutant libraries to find the best-suited clones according to well-defined selection criteria ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…47 Such moieties are also present in PaDa-I, but to the best of our knowledge such deactivation studies have not yet been performed on PaDa-I. 39,48 It was hoped that by employing the Lindlar catalyst no alkene reduction would be observed. Unfortunately, the double bond in styrene is likely too active and reduction of this moiety is observed, particularly at longer reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have also explored how to enhance stability and how to expand the substrate promiscuity of this versatile biocatalyst by structure-guided evolution [12] and neutral genetic drift [13]. Consequently, we believe that the extensive portfolio of UPO variants we have generated in recent years is likely to open new avenues for the more efficient synthesis of HDMs.…”
Section: Introductionmentioning
confidence: 99%